Injectable Polymer‐Nanoparticle Hydrogel for the Sustained Intravitreal Delivery of Bimatoprost. Issue 2 (31st October 2022) - Meany, Emily L.; Andaya, Roxanne; Tang, Shijia; Kasse, Catherine M.; Fuji, Reina N.; Grosskopf, Abigail K.; d'Aquino, Andrea L.; Bartoe, Joshua T.; Ybarra, Ryan; Shelton, Amy; Pederson, Zachary; Hu, Chloe; et al.
Abstract: Vision impairment resulting from chronic eye diseases, such as macular degeneration and glaucoma, severely impacts patients' quality of life and poses an immense global financial burden. Current standard of care for such diseases includes daily eye drops or frequent intravitreal (ITV) injections, which are burdensome treatment modalities resulting in low patient compliance. There remains a growing need for easily administered long‐acting delivery technologies for prolonging exposure of ocular therapeutics with each administration. Here, this work deploys a supramolecular polymer‐nanoparticle (PNP) hydrogel for ITV delivery of the glaucoma drug bimatoprost. PNP hydrogels are shear‐thinning and self‐healing, key properties for injectability, and enable slow release of molecular cargo in vitreous humor (VH) mimics. An in vivo study in New Zealand white rabbits demonstrated intravitreally injected PNP hydrogels form depots that degrade slowly over time, maintaining detectable levels of bimatoprost in the VH up to 8 weeks following injection. Ophthalmic examinations and histopathology identified a mild foreign body response (FBR) to the hydrogel, characterized by rare clusters of foamy macrophages and giant cells associated with minimal, patchy fibroplasia. This work shows that PNP hydrogels exhibit numerous desirable traits for sustained drug delivery and further work will be necessary to optimize tolerability in the eye. Abstract : Here, this work evaluates polymer‐nanoparticle (PNP) hydrogels as long‐acting delivery vehicles following intravitreal injection. These materials prolong the retention and delivery of model cargo and glaucoma drug bimatoprost following injection into model vitreous humor (VH) in vitro and maintain detectable levels of bimatoprost in rabbits for up to 8 weeks following intravitreal administration.